Address to the Board of Governors Meeting in Seoul, Korea - Clausen, A. W. (World Bank, Washington, DC, 2017)
In his speech, President A. W. Clausen reviews the economic and debt crisis of the last five years and shares his expectations for the next five years. The World Bank will play a vital role in a successful transition from recession to sustained economic growth. The Bank’s operational strategy rests on twin pillars: assisting borrowers in formulating adjustment programs, and helping mobilize external resources to sustain these programs. Heavily indebted middle-income countries need help to grow out of their debts. Poor countries in Sub-Saharan Africa need help analyzing and overcoming the constraints on their economic and social growth. Clausen submitted a resolution to establish the Multilateral Investment Guarantee Agency (MIGA). As an international community, we must undertake to reverse the depletion of our forests and the associated degradation of the land. Sustainable growth requires true development of human capital, the alleviation of poverty, and the maintenance of the environment. Improving the quality of life of all who dwell in the developing nations has more dimensions than ever before.